1978
DOI: 10.1128/jb.133.2.621-625.1978
|View full text |Cite
|
Sign up to set email alerts
|

sn-Glycerol-3-phosphate dehydrogenase and its interaction with nitrate reductase in wild-type and hem mutant strains of Staphylococcus aureus

Abstract: Staphylococcus aureus has membrane-associated sn-glycerol-3-phosphate dehydrogenase activity that is strongly activated by detergents. The enzyme can be measured spectrophotometrically in intact cells in assay systems containing lauryldimethylamine oxide (Ammonyx LO). The dehydrogenase activity was located exclusively in the membrane fraction of cells grown with glycerol under aerobic conditions or under anaerobic conditions with the addition of nitrate; there was no evidence of multiple forms. Development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…56 Four enzymes are involved in glycero-phospholipid metabolism (spots 8-10, 82, 83, 96, and 122) such as the glycerol-3phosphate dehydrogenase which is also membrane-associated in S. aureus. 57,58 Three proteins are directly involved in cell wall biogenesis and in peptidoglycan biosynthesis (spots 17, 18, 33, 34, and 95) for example, UDP-N acetylglucosamine transferases. 59 Interestingly, some membrane proteins involved in carbohydrate metabolism could also be involved in cell wall biogenesis such as glucose-6-phosphate isomerase (spots 16 and 17) as shown in Mycobacterium smegmatis, 60 or lactate dehydrogenase (spots 59, 60-76) considering L-lactate could be a cell wall component as observed in Lactobacillus plantarum.…”
Section: Resultsmentioning
confidence: 99%
“…56 Four enzymes are involved in glycero-phospholipid metabolism (spots 8-10, 82, 83, 96, and 122) such as the glycerol-3phosphate dehydrogenase which is also membrane-associated in S. aureus. 57,58 Three proteins are directly involved in cell wall biogenesis and in peptidoglycan biosynthesis (spots 17, 18, 33, 34, and 95) for example, UDP-N acetylglucosamine transferases. 59 Interestingly, some membrane proteins involved in carbohydrate metabolism could also be involved in cell wall biogenesis such as glucose-6-phosphate isomerase (spots 16 and 17) as shown in Mycobacterium smegmatis, 60 or lactate dehydrogenase (spots 59, 60-76) considering L-lactate could be a cell wall component as observed in Lactobacillus plantarum.…”
Section: Resultsmentioning
confidence: 99%
“…9A), menaquinone receives electrons directly from a large number of membrane dehydrogenases including glycerol-3-phosphate dehydrogenase, succinate dehydrogenase, the menaquinone oxidase complex, LDH and an NDH2, which in turn receives electrons from at least two solu-ble enzymes: alcohol dehydrogenase and the PDC. In mitochondria LDH and glycerol-3-phosphate dehydrogenase do not donate electrons to the respiratory chain, yet in bacteria they are membrane-bound enzymes transferring their electrons directly to ubiquinol (Barnes and Kaback 1970;Lascelles 1978;Doig et al 1999;Modun and Williams 1999;Dym et al 2000;Delgado et al 2001;Fuller et al 2011). From menaquinone, electrons are transferred to one of two terminal O 2 -dependent oxidases, namely, cytochrome bo and cytochrome aa 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The response regulator NreC is subsequently phosphorylated by NreB and specifically binds to the promoters of the narT gene and of the narGHJI and nirBD operons to activate transcription [ 37 39 ]. Since previous studies have shown that both aerobic and anaerobic G3P dehydrogenase can transfer hydrogens from G3P to nitrate, leading to growth of E. coli and S. aureus on glycerol as the carbon source and nitrate as the hydrogen acceptor [ 40 , 41 ]. We speculate the gdpS gene may negatively modulate the entire respiratory pathway consisting of glycerol catabolism and nitrate reduction in S. epidermidis .…”
Section: Resultsmentioning
confidence: 99%